2020
DOI: 10.1921/gpwk.v29i2.1213
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Sexual Self-efficacy of Sexual and Gender Minority Youth through a Group Intervention

Abstract: The current study examined the efficacy of an affirmative group cognitive behavioral intervention on the sexual self-efficacy level of sexual and gender minority youths (SGMY). SGMY (n=30) between the age of 15 and 18 participated in a series of eight cognitive behavioral-focused groups. They also completed measures on sexual self-efficacy before and after the intervention. Paired sample t-test was chosen as method of analysis. The results indicated a statistically significant increase in protection sexual sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some scoping review and systematic review studies find that group work is commonly used in intervention programs for promoting child development in health (Wang, Victor et al, 2020), mental health (Wang, Sokol et al, 2020), and resilience (Wang, Zhang et al, 2021). In addition, it is also utilized and found to be effective in programs of self-recognition (e.g., Hayashi & Takahashi, 2017), self-efficacy (e.g., Bohecker & Doughty Horn, 2016; Craig et al, 2020), and confidence (Macgowan & Wong, 2017) improvement and found with effectiveness. This study proposes to implement group work aiming to promote the self-recognition, self-efficacy, and confidence of KCw/oSPC.…”
Section: The Present Studymentioning
confidence: 99%
“…Some scoping review and systematic review studies find that group work is commonly used in intervention programs for promoting child development in health (Wang, Victor et al, 2020), mental health (Wang, Sokol et al, 2020), and resilience (Wang, Zhang et al, 2021). In addition, it is also utilized and found to be effective in programs of self-recognition (e.g., Hayashi & Takahashi, 2017), self-efficacy (e.g., Bohecker & Doughty Horn, 2016; Craig et al, 2020), and confidence (Macgowan & Wong, 2017) improvement and found with effectiveness. This study proposes to implement group work aiming to promote the self-recognition, self-efficacy, and confidence of KCw/oSPC.…”
Section: The Present Studymentioning
confidence: 99%